APPLICATION OF INTELLECTUAL CAPITAL DISCLOSURE IN PRIVATE UNIVERSITIES IN INDONESIA - Dedy Abidin; Anna Sutrisna Sukirman; Syamsinar, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Recognition of intellectual capital (IC) is an effort to increase organizational value and competitive advantage (Chen et al., 2005). The term IC is a combination of intellectual and capital that indicates the importance of knowledge (Lev & Zarowin, 1999; Serenko & Bontis, 2013), especially in universities where the main capital is resources in the form of knowledge owned by the entire academic community of universities. In particular, intellectual capital disclosure (ICD) can be a very effective means for companies to signal quality excellence due to the importance of intellectual capital for future wealth creation (Guthrie & Petty, 2000). Especially for companies with a strong intellectual capital foundation, intellectual capital disclosure is able to distinguish low-quality companies (An et al., 2011). The research method used is mixed-method analysis. The data used in this study are primary and secondary. Primary data is in the form of interviews with the in-depth interview method, with the aim of supporting research results from secondary data in the form of financial statements that have been prepared by universities. The universities used in this research as a pilot project are private universities that have been accredited and have sustainable financial reports. The result of this study is the compilation of items from three components of intellectual capital, which are the basis for the item of Intellectual Capital Disclosure of Higher Education in Indonesia, which is adjusted to BAN PT and Lamemba.